1963
DOI: 10.1017/s0021859600011412
|View full text |Cite
|
Sign up to set email alerts
|

Shorn and unshorn Awassi sheep I. Body temperature

Abstract: 1. The rectal temperatures of shorn and unshorn Awassi sheep were measured at various hours of the day and during various seasons of the year in two different locations in Israel.2. An increase in body temperature accompanied an increase in environmental temperature. A steeper temperature increase was noted in shorn sheep kept in the shade. When ambient temperatures were below 30° C. the body temperature of shorn sheep was lower than that of the unshorn sheep by an average of 0·16° C.3. When ambient temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Previous long-term studies of the deep body temperature patterns of sheep have varied widely in technique, experimental regime and location, and the breed studied, but the results agree well with the essential points reported here. Eyal (1963), in his studies of the nychthemeral variations in rectal temperature of shorn and unshorn Awassi sheep during summer and winter, and in sunshine and shade, in Israel, found a monophasic nychthemeral variation of less than 10 C in all these circumstances, with the lowest temperature in the early morning and the highest in the evening. Minett & Sen (1945), Miller & Monge (1946) and Veeraraghavan & Mendel (1963) have also reported similar monophasic nychthemeral variations in the rectal temperature of different breeds of sheep.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous long-term studies of the deep body temperature patterns of sheep have varied widely in technique, experimental regime and location, and the breed studied, but the results agree well with the essential points reported here. Eyal (1963), in his studies of the nychthemeral variations in rectal temperature of shorn and unshorn Awassi sheep during summer and winter, and in sunshine and shade, in Israel, found a monophasic nychthemeral variation of less than 10 C in all these circumstances, with the lowest temperature in the early morning and the highest in the evening. Minett & Sen (1945), Miller & Monge (1946) and Veeraraghavan & Mendel (1963) have also reported similar monophasic nychthemeral variations in the rectal temperature of different breeds of sheep.…”
Section: Discussionmentioning
confidence: 96%
“…Eyal (1963), however, found remarkably little difference in the thermoregulatory behaviour of shorn and unshorn sheep. In the study reported here, the Welsh Mountain sheep did not always use the shelter when the weather was bad.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…An increase in rectal temperature was reported under heat and water stress (Alamer and Al-hozab, 2004;Eyal, 1963;MacFarlane, 1964;Taneja, 1965) while others reported no variation in rectal temperature (Hamadeh et al, 2006;Jaber et al, 2004). The slight increase in rectal temperature may be an attempt to decrease water losses by evaporative cooling (Silanikove, 1992).…”
Section: Article In Pressmentioning
confidence: 96%